Continuous-wave and passively Q-switched 1.06 μm ceramic Nd:YAG laser. (July 2016) - He, Ying; Ma, Yufei; Li, Jiang; Li, Xudong; Yan, Renpeng; Gao, Jing; Yu, Xin; Sun, Rui; Pan, Yubai
Abstract: In this paper, a diode-pumped continuous-wave and passively Q-switched 1.06 μm laser with gain medium of ceramic was demonstrated. Laser output characteristics using Nd:YAG ceramics with different doping concentrations of 1.0%, 2.0%, and 4.0% were studied. A maximum output power of 7.74 W with optical efficiency of 51.6% was obtained through the optimization of the coupler's transmission. By using Cr 4+ :YAG crystals with initial transmissions of 80% and 90% as saturable absorbers, the pulsed ceramic Nd:YAG laser performance was investigated. Highlights: A diode-pumped Nd:YAG ceramic laser was demonstrated. The high Nd 3+ doping concentration of the ceramic laser was studied. The continuous-wave and passively Q-switched performance was investigated.